An investigation of the surface quality of burnished AISI 4340 steel. (June 2018) - Boozarpoor, Mehrzad; Elyasi, Majid; Hosseinzadeh, Morteza
In the present work, an attempt is made to study the predominant factors of ball burnishing namely, burnishing speed, burnishing feed, burnishing force, and pass number on the surface roughness, surface hardness, and out-of-roundness error of hard-turned AISI 4340 rods. Response surface methodology was used to correlate the empirical relationship between the process factors and responses. Also, the minimum surface roughness, out-of-roundness error, as well as the maximum hardness were taken into consideration for finding the optimal parameter setting. Analysis of variances was also performed to check the adequacy of the developed models. Results indicated that the most influential parameters for the surface roughness and roundness error is the burnishing feed. Also, for surface hardness, it was found that the pass number had the greatest influence. It was further seen that a burnishing speed of 150 r/min, burnishing feed of 0.16 mm/rev, burnishing force of 24.5 N, and pass number 4 yields the desirable burnishing quality characteristics. The obtained results were then validated through performing morphological study and microstructural observation of the burnished surface.